Physico-Chemical Characterisation and Determination of Luteolin Content of Pidada merah (Sonneratia Caseolaris L) Leaf Extract - Syamsul, Eka Siswanto; Lestari, Dwi; Dachriyanus, Dachriyanus; Supomo, Supomo (Sciences of Pharmacy, 2026)
Red pidada (Sonneratia caseolaris L.) leaves are used traditionally for skin care and other medicinal purposes. This study aimed to characterise the powdered leaf material and determine the luteolin content of the ethanolic leaf extract. Dried leaf powder was macerated with 95% ethanol. The powdered material was characterised by macroscopic and microscopic examination and by determining the water-soluble extractive value, ethanol-soluble extractive value, moisture content, total ash, and acid-insoluble ash. Metabolite profiling of the extract was performed using high-resolution liquid chromatography-mass spectrometry (HR-LCMS). Luteolin content was estimated by TLC-densitometry using silica gel 60 F254 plates and n-hexane: ethyl acetate (2:3) as the mobile phase. Macroscopically, the leaves were oval to elongated with rounded to blunt apices, entire margins, pinnate venation, and a dark-green colour. Microscopic examination showed upper and lower epidermal tissues, stomata, and vascular bundles. The powdered leaves had a bitter taste. The water-soluble and ethanol-soluble extractive values were 11% and 16%, respectively, while the moisture content, total ash, and acid-insoluble ash were 8.8%, 8.12%, and 0.47%. HR-LCMS generated 38 tentative database matches, including luteolin. Under the assay conditions used, TLC-densitometry showed an Rf value of 0.54 for luteolin and a mean measured luteolin amount of 3.849 µg. These findings provide baseline physicochemical and preliminary phytochemical data for the standardisation of Sonneratia caseolaris L leaf extract.